Laser Treatment of Peri-Implantitis: A Literature Review - Ashnagar, Sajjad; Nowzari, Hessam; Nokhbatolfoghahaei, Hanieh; Yaghoub Zadeh, Behnoush; Chiniforush, Nasim; Choukhachi Zadeh, Nastaran (Journal of Lasers in Medical Sciences, 2014)
Peri-implantitis is a state defined as an inflammatory reaction around osseointegrated implants, leading to progressive loss of supporting bone. Various treatment methods are suggested in the treatment of peri-implantitis and clinicians have to choose a method over a large number of treatment protocols. Lasers have shown promising therapeutic effect in treatment of peri-implantitis. However, some controversies have been found in clinical outcomes after using lasers. Therefore, we aimed to review the current literature over the past ten years for the use of lasers in treatment of peri-implantitis, via the Pubmed electronic database of the US National Library of Medicine. Fifteen human studies were reviewed. Er:YAG (Erbium-Doped Yttrium Aluminum Garnet), CO2(Carbon Dioxide Laser) and Diode lasers were used. Despite inconsistencies and disharmonies among studies in terms of study design, positive treatment outcomes were obvious among the majority of them. However, short period of follow-ups and poor control of plaque index, as a critical confounding factor, were the major problems which these studies suffered from. It seems that one session laser therapy is not adequate for achieving optimal clinical outcome. Further studies with longer periods of follow-ups, intense control of plaque index, and various sessions of laser treatments are needed to clearly illustrate the clinical privilege of laser therapy.